Patient deterioration - Ndlovu, Joseph Mzingaye; Jaravaza, Ester; Mhlanga, Maxwell; Zvinavashe, Mathilda; Kasu, Christine; Makoni, Petty (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2018)
ABSTRACT In every health institution the possibility of patient deterioration is inevitable, however, the total outcome whether positive or negative depends on early identification of deterioration signs which are physical, emotional, psychological, social and spiritual domains. In most cases the health workers focus and document physiological signs of deterioration. A human being is holistic in nature has social, emotional, spiritual, psychological and physical needs that need to be attended to in cases of deterioration. Methodology The concept analysis of patient deterioration was done using the eight (8) strategic methods and literature search was done using the following search engines Google scholar, Pubmed, Medline. Initially twenty five (25) articles from 2002 to 2018 were reviewed. Fourteen (14) were later dropped due to their irrelevant information. The authors settled on twelve (11) articles. Results The majority of the authors dwelt much on physiological signs of deterioration not considering the emotional, psychological, social and spiritual domains. Conclusion The response to patient deterioration calls for holistic approach to ensure maximum care regardless of patient outcome. Skills and experience of health personnel are also important in detecting patient deterioration.